Persuasive multimedia in truancy awareness (PMTA): Integration of persuasive design principles - Dolhalit, Mohamad Lutfi; Azman, Farah Nadia; Abdul Salam, Sobihatun Nur; Abdul Mutalib, Ariffin; Yusoff, Muhamad Saiful Bahri (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
This article reports on the ongoing research which focuses on the use of persuasive design principle in the design and development of multimedia learning application for truancy awareness (PMTA). Primarily, this paper emphasizes on how persuasive design principle can be employed into a multimedia learning environment in fostering truancy awareness. This paper is presented in the following order; firstly, the current situation regarding truancy issues is explained. Next, the current practices on how to handle truancy issues are highlighted. The third part discusses the theoretical framework and how the principles were applied in designing the information and presentation of PMTA. In conclusion, it is hoped that PMTA would be a beneficial tool for rising truancy awareness and reducing this problem in Malaysia. The next step of this study will involve with experimental testing to evaluate the effects of the persuasive multimedia applications toward truancy awareness.